2020
DOI: 10.14742/ajet.6164
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors for implementing learning analytics in higher education: A mixed-method inquiry

Abstract: Critical success factors (CSFs) have been around since the late 1970s and have been used extensively in information systems implementations. CSFs provide a comprehensive understanding of the multiple layers and dimensions of implementation success. In the specific context of learning analytics (LA), identifying CSFs can maximise the possibilities of an effective implementation and harness the value of converting data into actionable information. This paper proposes a framework that aims to identify and explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Also, TEL-based Education (digitized-education) have attained flexibility and mobility in its mode of delivery or paradigms (Aguilera-Hermida et al, 2021;Diaz-Nunez et al, 2021;Okoye et al, 2021;del Rio-Chillcce et al, 2021;TEC, 2020b). This ranges from the innovative (pedagogical) frameworks or theories for teaching (Exter et al, 2019;Ndukwe & Daniel, 2020;Okoye et al, 2022), to the integration of educational technologies (EdTech) that are used to bridge the gap between the modern and traditional models for teaching/learning Shambour & Abu-Hashem, 2022), and in turn, provides new paradigms or practices for achieving sustainability and scalability in the use of EdTech for teaching or educational purposes (Clark et al, 2020;Okoye et al, 2021Okoye et al, , 2022Tondeur et al, 2020;UNESCO, 2015UNESCO, , 2021bYu & Jo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also, TEL-based Education (digitized-education) have attained flexibility and mobility in its mode of delivery or paradigms (Aguilera-Hermida et al, 2021;Diaz-Nunez et al, 2021;Okoye et al, 2021;del Rio-Chillcce et al, 2021;TEC, 2020b). This ranges from the innovative (pedagogical) frameworks or theories for teaching (Exter et al, 2019;Ndukwe & Daniel, 2020;Okoye et al, 2022), to the integration of educational technologies (EdTech) that are used to bridge the gap between the modern and traditional models for teaching/learning Shambour & Abu-Hashem, 2022), and in turn, provides new paradigms or practices for achieving sustainability and scalability in the use of EdTech for teaching or educational purposes (Clark et al, 2020;Okoye et al, 2021Okoye et al, , 2022Tondeur et al, 2020;UNESCO, 2015UNESCO, , 2021bYu & Jo, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the implications of this study, both in practice and the wider spectrum of scientific research and/or educational technologies, in particular, we note that prior studies have looked at the effect that educational technologies, such as the teaching analytical methods, have on the teaching perspectives and experiences for the students (Boring, 2017 ; Engen, 2019 ; Gallego-Arrufat et al, 2019 ; Gomes & Ma, 2020 ; Gordillo et al, 2019 ; Ndukwe & Daniel, 2020 ; Silva et al, 2019 ). Whereas some of the existing studies argued that the students evaluation of teaching (SET) may not necessarily be the most effective way of determining the teachers’ teaching performances and assessment (Boring, 2017 ; Gomes & Ma, 2020 ), other studies have also highlighted the early indicators or success factors that have been achieved over the years, particularly through the use of the educational technologies and data to support the teaching–learning processes and development (Bowdre, 2020 ; Clark et al, 2020 ; Engen, 2019 ; Hilliger et al, 2020 ; Kori et al, 2018 ; Oyedotun, 2020 ; Raffaghelli et al, 2020 ; Silva et al, 2019 ). To note, Engen ( 2019 ) mentioned that, there is now more than ever, the necessity for ample understanding of the emerging methods and digital technologies, both in terms of what can be called the cultural-to-social aspects for use by the educators, in fostering an effective teachers-students learning processes and experience (Dimitriadis et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, examples of operational use of Learning Analytics techniques are emerging as evidenced by Ifenthaler and Yau's review (2020). Clark et al (2020) identified and validated five critical success factors for the implementation of Learning Analytics at universities, including strategy and policy at an organisational level. If an objective approach to comparing universities using techniques drawing on the Learning Analytics field is to be developed, it will require strategy and policy above the level of individual institutions.…”
Section: How To Measurementioning
confidence: 99%